Analysis and Comparison of SVPWM and SPWM Methods Used for Indirect Rotor Flux-Oriented Control of EV Applications - Monadi, Mehdi; Astaraki, Amir Arsalan; nia, Pouria Changalvaie (Journal of power technologies, 2024)
Nowadays, electric vehicles (EVs) are considered one of the best solutions to reduce fossil-fuel usage in the transportation industry. In EV applications, due to the cost and maintenance problems, induction motors (IMs) are exciting option over DC motors. Therefore, IM power-electronic-based drives are the EVs most essential components which need more consideration and investigation. One of the effective and well-known control methods in AC electric motor drives is the indirect rotor flux-oriented control (IRFOC) method. The IRFOC method controls the electromagnetic torque and rotor flux independently. The IRFOC method should be equipped with a proper switching technique to reduce power losses, disturbances, voltage/current distortions, etc. The Sinusoidal Pulse Width Modulation (SPWM), and Space Vector Pulse Width Modulation (SVPWM) methods are of the available switching methods for electric motor drives. Few studies have been conducted to compare these two switching methods, but less focus has been on their effects on EV performance when a vehicle’s parameters, such as load torque, are changed. In this paper, the mentioned switching strategies are simulated to control a 50 hp, 460V three-phase induction motor. The required simulations were done in the MATLAB/ Simulink software, and several scenarios were considered to compare the performance of SPWM and SVPWM methods in terms of speed tracking, disturbances created by the drive converter, efficiency, input and output power, required DC battery, and the EV motor stability under load change. The merits and drawbacks of these two switching methods are also described in detail.